Perception of risk of HIV/AIDS among widows using the Ndlovu Medical Centre, Elandsdoorn, Limpopo Province - Amosun, Durotolu Motunrayo (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2011.